# Algebra Hardest Exam: Trivia Quiz

50 Questions | Total Attempts: 84  Settings  .

Related Topics
• 1.
Solve and simplify: 42 + 8 (-3) / -4 =
• A.

16

• B.

18

• C.

20

• D.

22

• 2.
Solve and simplify: [2 (-5) (-3)] / [2 (-3) – 3 (-3)] -1 =
• A.

7

• B.

8

• C.

9

• D.

10

• 3.
Solve and simplify: 1220 x 3 =
• A.

366

• B.

0

• C.

3

• D.

5

• 4.
Evaluate the expression, given x = -½  y = -2, z = -3 3x – y – 2z / 4 =
• A.

1

• B.

2

• C.

3

• D.

4

• 5.
The absolute value of -(300) is 300.
• A.

True

• B.

False

• 6.
Simplify the following expression:
• 7.
Solve and simplify the following problem:
• A.

5

• B.

10

• C.

15

• D.

20

• 8.
The number of flowers in a vase is an infinite number.
• A.

True

• B.

False

• 9.
Express the following phrase algebraically:  The product of a number and 6
• A.

6 / x

• B.

6 (x)

• C.

6

• D.

X

• 10.
Express the following phrase algebraically:  A number divided by 3
• A.

X / 3

• B.

3x

• C.

4 / 3

• D.

0

• 11.
(3) ((-2)2 + 1) = ?
• A.

-9

• B.

12

• C.

15

• D.

18

• 12.
Evaluate and simplify the expression: a = -2; b = 3; c = -5 a + b (c) = ?
• A.

-6

• B.

6

• C.

-13

• D.

-17

• 13.
Evaluate and simplify the expression: a = -2; b = 3; c = -5 ba / c = ?
• A.

-9/5

• B.

-9/45

• C.

-1/45

• D.

-1/5

• 14.
Evaluate and simplify the expression: a = -2; b = 3; c = -5 b + 2c
• A.

-12

• B.

8

• C.

-7

• D.

2

• 15.
Jack ate four pork chops.  Ron ate twice as many.  How many pork chops did they eat in total?
• A.

8

• B.

10

• C.

12

• D.

14

• 16.
Jane saw four tigers eating three antelope each. Each antelope had two antlers. Each antler had three spots on one side and two on the other. Both the tigers and antelope were in the rain, when six inches of water flooded their homes. Each of their homes were on stilts built seven feet high over a river. How many spots were on the antlers?
• 17.
Solve and simplify:  ((32b2) (32a2) )1/2 = ?
• 18.
((8a)(27a2))1/3 = ?
• 19.
(8a3/125a6)1/3 = ?
• 20.
The time came for the elephant to show off his stunt.  He did four tricks in the first five minutes, but twice as many in the next five minutes.  How many tricks did he do in ten minutes?
• 21.
Jon had five apples.  He then went to the store where he bought three times as many before selling half of his total.  Jack then gave him three times as many as he already had.  Jon then threw one away, before buying three oranges from the local grocery store and selling half of these.  How many oranges did Jack have remaining?
• 22.
A dollar bill was accidentally torn into five parts, with each part having one blue dot and two yellow dots on it.  How many dots were on the dollar bill, altogether?
• 23.
Which property is shown in the following problem? 22 + 23 = 23 + 22
• A.

Associative

• B.

Commutative

• C.

Distributive

• D.

Identity

• 24.
Which property is shown in the following problem?  (2 + 3) + 4 = 2 + (3 + 4)
• A.

Associative

• B.

Commutative

• C.

Distributive

• D.

Identity

• 25.
Which property is shown in the following problem?  4 (2c – a) = 8c – 4a
• A.

Associative

• B.

Commutative

• C.

Distributive

• D.

Identity